ANALYSIS OF THE MODEL OF MEMORALBE TOURISM EXPERIENCE AND DESTINAION ATTRIBUTES ON THE REVISIT INTENTION - Dabphet, Siripen (Journal of MCU Social Science Review, 2022)
The study aims to examine memorable tourism experience in tourism destinations and to analyze the linkage model of memorable tourism experience, destination attributes and intention to visit value on Lower Northern 1 region. The study used a quantitative research approach. A self-administered questionnaire is developed and distributed to 400 domestic tourists visiting Lower Northern 1 region. Data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The results reveal that all of 3 hypotheses are accepted. This means that destination attributes have significant influence on memorable tourism experience at the significant level at .01, memorable tourism experience has significant influence on revisit intentions at the significant level at .01 and destination attributes have significant influence on revisit intentions at the significant level at .05.